The Influence of Technological Literacy on Employee Performance at the South Sulawesi Agricultural Modernization Implementation Center: JEL Classification: M12, M15, J24, O33, H83 - Masdar Mas’ud; Hastuti Mulang; Hasnawati Hasnawati (Newinera Publisher, 2026)
This study aims to analyze the influence of technological literacy, competence, and work discipline on employee performance at the Agricultural Modernization Implementation Center (BRMP) of South Sulawesi. This research employed a quantitative method with a survey approach. The population of this study consisted of all employees of BRMP South Sulawesi, with a total sample of 50 respondents determined using a saturated sampling technique. Data were collected through questionnaires using a Likert scale and analyzed using SPSS version 23. The data analysis techniques included validity testing, reliability testing, classical assumption tests, multiple linear regression analysis, t-test, F-test, and coefficient of determination test. The results of the study indicate that technological literacy, competence, and work discipline simultaneously have a positive and significant effect on employee performance with a significance value of 0.000. Partially, technological literacy has a positive and significant effect on employee performance with a significance value of 0.000. Competence also has a positive and significant effect on employee performance and is the most dominant variable with a regression coefficient value of 0.634 and a significance value of 0.000. Work discipline also has a positive and significant effect on employee performance with a significance value of 0.008. The coefficient of determination (R²) value of 0.897 indicates that 89.7% of the variation in employee performance can be explained by these three variables, while the remaining 10.3% is influenced by other variables outside this study.